Assessment of durum wheat (Triticum durum) genotypes on grain filling parameters - MOHAMED BADR ISLAM, DJOUDI; KHALISSA, CHENITI; ALI, GUENDOUZ; NASSREDDINE, LOUAHDI; HAROUN, BELGUET (The Indian Journal of Agricultural Sciences, 2023)
Durum wheat (Triticum durum Desf.), a crucial crop in the Mediterranean basin, faces challenges due to drought, resulting in substantial yield losses. This study was carried out during the winter (rabi) season of 2020–2021 to determine the influence of grain filling parameters on individual grain weight variation and their relationship to yield components in 3 durum wheat genotypes (Boussellam, Oued El-Bared and GTA-dur) grown at 3 different locations with varying rainfall patterns under a semi-arid condition of Algeria. Samples were collected from each genotype on 9 different dates to assess grain number, dry weight and grain filling parameters. The experimental results revealed significant genotype effects on grain yield, 1000-kernel weight and most grain filling parameters across all 3 locations, except for the parameter SFR (supreme fill rate). Boussellam recorded higher grain yield, kernel weight and maximum final weight parameter (MFW) due to its longer grain filling duration and higher rate of grain filling. Linear regression analysis indicated decrease of 0.001 mg/day in the rate of grain filling led to a loss of 0.9527 mg in the maximum final weight. Correlation analysis highlighted the interdependence between the rate and grain filling duration, which varied across different environments and influenced dry-matter accumulation, ultimately led to higher grain yield.